Knowledge of breastfeeding among female college students: institution based cross-sectional study - Brahmbhatt, Krutarth R.; Chandana, G.; Vishwanath, Jayamala; Raman, Rupesh; S., Jayaram; Mallya, Sreelakshmi; Shetty, Harshali; D’Silva, Rithi; Shetty, Sharanya (International Journal Of Community Medicine And Public Health, 2017)
Background: Understanding of young women’s attitudes towards BF should be an early step in the design and implementation of BF interventions. There is a need for breastfeeding promotion strategies among female students to encourage them, in the future, to breastfeed and also champion the cause of breastfeeding as a child survival strategy. This study was conducted to assess knowledge of breastfeeding among female college students and to study factors associated with knowledge of breastfeeding. Methods: This was an institution based cross-sectional study conducted in August to October 2015. A validated structured questionnaire was used to assess knowledge of breastfeeding among female degree college students. Sample size derived was 580. Complete enumeration was done of all the students from the selected colleges. P-value <0.05 was considered statistically significant. Binary logistic regression analysis (enter method) was performed to find out the effect of co-variates on breastfeeding knowledge. Results: Total 630 students participated in the study. Approximately 66% of the students had adequate knowledge regarding breastfeeding. As per logistic regression analysis mother being a housewife and living in a nuclear family were predictors for higher breastfeeding knowledge among participants. Conclusion: There is a great scope for improving adolescents’ knowledge of breastfeeding in colleges.